Tantangan Manajemen Sekolah dalam Tata Kelola di Maahad Integrasi Tahfiz Sains Selangor - Ainul Hayat Abdul Rahman; Fakhri Sungit; Zetty Nurzuliana Rashed (JUDICIOUS, 2021)
Quality education is often associated with quality school governance. However, establishing and establishing effective management in schools is very difficult. This is because schools are different from other organizations. However, efforts to produce an educated society will be more successful if all the problems, challenges and problems that exist in schools can and can be overcome. This study aims to identify the challenges found in the management of governance in schools, analyze the challenges faced in the aspects of curriculum management in schools and examine the challenges faced by schools in terms of school facilities and infrastructure. This research is a qualitative research that involves interviews with research participants. The results of the study found that there are various major challenges faced by school management that need to be addressed immediately. There are various challenges and issues of education management that can be categorized in terms of administration, education level, facilities and infrastructure, school organization and teacher professionalism. Therefore, diligent efforts and cooperation from various parties will produce an effective and quality school governance management system that is able to face all current challenges holistically. These obstacles and challenges need to be addressed wisely so that the image of the world of education management in Malaysia is not tarnished by the issues that arise.